Single mimivirus particles intercepted and imaged with an X-ray laser - CXIDB ID1 - Maia, Filipe (Uppsala University, 2020)
These are the files used to reconstruct the images in the paper “Single Mimivirus particles intercepted and imaged with an X-ray laser” (2011).

Besides the diffracted intensities, the Hawk configuration files used for the reconstructions are also provided.

More information and data at Coherent X-ray Imaging Data Bank.

The files used to reconstruct the images in the paper “Single Mimivirus particles intercepted and imaged with an X-ray laser” (2011).
Besides the diffracted intensities, the Hawk configuration files used for the reconstructions are also provided.

The files from CXIDB ID 1 are the pattern and configuration files for the pattern showed in Figure 2a in the paper.

Datasetet består av de data som ligger till grund för bilderna i artikeln “Single Mimivirus particles intercepted and imaged with an X-ray laser” (2011).

För mer information se den engelska katalogsidan (https://snd.gu.se/en/catalogue/study/ext0308) och posten för data hos Coherent X-ray Imaging Data Bank.

Filerna som används för att rekonstruera bilderna i artikeln "Single mimivirus particles intercepted and imaged with an X-ray laser" (2011).
Single mimivirus particles intercepted and imaged with an X-ray laser - CXIDB ID1
Keywords: XFEL (free electron laser facility); XFEL (frielektronlaseranläggning); Atom and Molecular Physics and Optics; Atom- och molekylfysik och optik; Structural Biology; Strukturbiologi